Hygienic Assessment of Radioactive Deposition in the Territory of Tashkent (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article provides a hygienic assessment of radioactive fallout on the territory of Tashkent. Weight volume of atmospheric fallout in the city of Tashkent, no significant differences in the average volume of fallout on the territory of various elements of the city’s infrastructure were identified (16.3 ± 0.8 g per 1 m2 per day), but in the local area of the residential area and in the park area at some points they were noted significantly higher rates of atmospheric fallout (up to 21.3 g/ m2 per day); the average level of atmospheric radioactive fallout in Tashkent is 8.11±0.010 Bq/ m2 per day.